Pengaruh Aditif EM4 dan Gula Merah Terhadap Karakteristik Silase Rumput Gajah (Pennisetum purpureum) - Herlinae Herlinae; Yemima Yemima; Rumiasih Rumiasih (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
The aim of this research was to know the effect of additives EM4 and palm sugar on the characteristics of elephant grass (Pennisetum purpureum) silage. This research was designed using a 2 x 2 factorial experiment with completely randomized design. Results showed that the additives EM4 and palm sugar give a good influence in the characteristics of elephant grass silage include; smell, taste, color, and texture. There is no interaction between the use of additives EM4 and palm sugar in making of elephant grass silage. Key words : Elephant grass, silage, palm sugar , additives